LESSON LEARN FROM IMPLEMENTATION OF THE INTEGRETED CRIMINAL JUSTICE SYSTEM – HANDLING VIOLENCE AGAINST WOMEN IN CENTRAL JAWA - yustina fendrita Christovani (ABDI HUMANIORA: Jurnal Pengabdian Masyarakat Bidang Humaniora, 2021)
This study wants to analyze the learning of Central Java province in implementing SPPT PKKT (Integrated Criminal Justice System for Handling Cases of Violence Against Women); By taking a case study in Central Java Province which has implemented SPPT PKKTP since 2014 - now. This study was proposed to answer the question How the Province of Central Java Implement SPPT PKKTP to access access to the court and to fulfill the rights of women victims of the struggle. This study proves that the first time the SPPT PKKTP was very effective in improving coordination and cooperation between Law Enforcement Officials and Service Institutions was very effective in bringing victims' rights closer to access to welfare, the second SPPT PKKTP was a collaborative work between the Central Java Regional Government and Organizations Civil Society and Third, the application of SPPT PKKTP is highly dependent on intensive escort and the assistance process of the National Commission on Violence Against Women and Civil Society Organizations (KJHAM), because the concept of SPPT PKKTP is Top Concepts that were developed in a participatory manner from the center to then be implemented at the regional level with the collaborative work patterns between the parties.